A thematic analysis of hospital medical records of patients with advanced illness experiencing incarceration in the last 3 months of life. (April 2023) - Le Gautier, Roslyn; Panozzo, Stacey; Bryan, Tamsin; Lethborg, Carrie; Philip, Jennifer
Background: The constraining prison culture is not, for the most part, conducive to the provision of palliative care for people in prison. Aim: This study aimed to explore patterns of palliative and end-of-life care provision for hospitalised prison patients. Design: A retrospective qualitative review of hospital medical records to explore the quality of end-of-life care provision for patients experiencing incarceration who died within hospital. Qualitative inductive analysis of record extracts of each patients final 3-months of life was undertaken. Setting/participants: An Australian metropolitan hospital responsible for providing secondary and tertiary health services for people experiencing incarceration. This study included a systematic sample of male patients experiencing incarceration who died in hospital between 2009 and 2019. Results: Medical record extracts of 15 male patients revealed two broad themes: (1) barriers to equitable access to palliative care for incarcerated hospitalised patients; and (2) factors that facilitated quality end-of-life care for patients and families. Barriers included: tensions between balancing risk and humanity; and limited agency over place and death. Conversely, early recognition of deterioration and anticipated dying provided patients and families opportunity to focus on end-of-life goals. Conclusions: Institutional influences of security and control challenged the provision of equitable end-of-life care for people experiencing incarceration. Further research is required to inform, and incorporate, best approaches to identifying patient wishes and advance planning into care within, or despite, the constrains of incarceration. Policy reform and a coordinated, best practice approach to the management of end-of-life care for people experiencing incarceration is needed.